DETERMINING THE RELATIONSHIP BETWEEN SOCIAL MEDIA APPEARANCE CONSCIOUSNESS AND SELF-ESTEEM IN ADOLESCENTS - Oluc, Tugba; Ayran, Gulsun (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2024)
Introduction: Adolescents' active use of social media raises curiosity about how they appear on social media platforms. This situation may cause changes in their personality. This study was conducted to determine the relationship between social media appearance consciousness and self-esteem in adolescents. Method: This cross-sectional study was conducted between January and March 2023. The study involved 1103 students from three different high schools located in a province in eastern Turkey. As part of the study process, data were collected using the "Questionnaire", "Appearance-Related Social Media Consciousness Scale" and "Rosenberg Self-Esteem Scale". To analyze the data, percentages, averages, independent sample t-tests, one-way ANOVA, Pearson correlation, and regression analysis were performed. The significance level in all tests was set at 0.05. Shao's method was employed to assess the conformity of the data to normal distribution. As a result, the Skewness value was 0.409, the Kurtosis value was -0.370, and it was determined that the data showed a normal distribution between -3 and +3. Results: The mean age of the students in the study was 26.8% 15 years old, 62.2% were male, and 27% were 9th-grade students. The mean total score of the students was 41.11±17.74 for the Appearance-Related Social Media Consciousness Scale and 29.36±6.35 for the Rosenberg Self-Esteem Scale. It was determined that there was a positive correlation between the scores of the Appearance-Related Social Media Consciousness Scale and the Rosenberg Self-Esteem Scale (p<0.05). Conclusions: In conclusion, it was observed that increasing social media appearance consciousness scores was associated with higher self-esteem levels.